Awareness and use of Open Access Resources among the Social Scientists: A Study of ICSSR Institutes in India - V Hegde, Pradeep (Journal of Information and Knowledge, 2017)
Social science research institutions play a vital role in society by way of creating, formulating public policies. This study focuses on social scientists’ approach to open access initiatives in India. A structured questionnaire was distributed among 288 faculty members of ICSSR institutes located all over India; 166 (58%) responses were received. The study findings show that, 67% of the respondents are aware of open access resources available in social science research arena, but are not very keen on publishing their research work in open access journals. Over 55% of the respondents have responded positively to citation of open access resources in their research publications. Visibility and free access are found to be the major advantages associated with open access journals, while expensive author publishing charge is the foremost hurdle to publishing articles in open access journals. Finally, the study concludes with the suggestion that OA publishers need to be more vibrant about maintaining the quality of research articles in addition to enlightening on the role of librarians in promoting the use of open access resources.